PENERAPAN KUOTA KETERWAKILAN PEREMPUAN PADA PEMILU 2019 DI KABUPATEN GOWA - Kavrianti, Nurlina; Sastrawati, Nila (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The policy of women's representation quota in the legislative nomination process is a form of gender-responsive policy to reduce the gap in access, participation, control, benefits and opportunities between women and men. This study aims to find out how to fulfill the quota for women's representation in the Dewan Perwakilan Rakyat Daerah (DPRD) of Gowa Regency, especially the results of the 2019 elections. This research uses qualitative methods with empirical and normative syar'i juridical approaches. The results showed that at the nomination stage, the application of the quota of 30% of women in each constituency by all political parties has been fulfilled, but only 13 people or 28.8% of the total 45 seats are successfully elected.